TrustedPals: Secure Multiparty Computation Implemented with Smart Cards - Fort, Milan; Freiling, Felix; Draque Penso, Lucia; Benenson, Zinaida; Kesdogan, Dogan (Computer Security - ESORICS 2006, 11th European Symposium on Research in Computer Security, 2006)
We study the problem of Secure Multi-party Computation (SMC) in a model where individual processes contain a tamper-proof security module, and introduce the TrustedPals framework, an efficient smart card based implementation of SMC for any number of participating entities in such a model. Security modules can be trusted by other processes and can establish secure channels between each other. However, their availability is restricted by their host, that is, a corrupted party can stop the computation of its own security module as well as drop any message sent by or to its security module. We show that in this model SMC can be implemented by reducing it to a fault-tolerance problem at the level of security modules. Since the critical part of the computation can be executed locally on the smart card, we can compute any function securely with a protocol complexity which is polynomial only in the number of processes (that is, the complexity does not depend on the function which is computed), in contrast to previous approaches. © Springer-Verlag Berlin Heidelberg 2006.
UnivIS-Import:2015-04-16:Pub.2006.tech.IMMD.lehrst.truste